MANAJEMEN BUDAYA SEKOLAH DI SMK NEGERI 3 KABUPATEN SELUMA - Hendri Hendri; Rohiat Rohiat; Aliman Aliman (UNIVERSITAS BENGKULU, 2018)
Abstract : The specific objectives of this study were to describe school culture management at public vocational school number 3 Seluma regency. This research uses qualitative descriptive method. The subjects of the study were principal, vice principal, and teachers. Techniques of collecting data using interviews, observation and documentation. The collected data was analyzed by using qualitative descriptive technique. The results show before the school culture development program implemented the school management is to make or make the school culture program planning.. Then the implementation of school culture development is done in principle to implement all the programs that have been prepared in a pure and consistent. And finally the evaluation to know the effectiveness adn effisiency of the program. Keywords: management, culture, cultural management Abstrak: Tujuan khusus penelitian ini adalah untuk mendeskripsikan manajemen budaya sekolah di SMKN 3 Kabupaten Seluma. Penelitian ini menggunakan metode deskriptif kualitatif. Subyek penelitian adalah kepala sekolah, wakil kepala sekolah, dan guru-guru. Teknik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Data yang terkumpul dianalisis dengan menggunakan teknik deskriptif kualitatif. Hasil penelitian menunjukkan pengembangan budaya sekolah dilaksanakan dengan membuat perencanaan program budaya sekolah, melaksanakan kegiatan yang telah direncanakan dengan baik. Dan selalu mengadakan evaluasi untuk mengetahui efektivitas dan efisiensi pembinaan. Kata Kunci: manajemen, budaya, manajemen budaya